Running intensities in elite youth soccer by age and position - Duthie, G. M.; Thornton, H. R.; Delaney, J. A.; Connolly, D. R.; Serpiello, F. R. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this investigation was to examine differences between the peak running speed, acceleration, and metabolic power of elite youth soccer across a range of age levels by position. Ninety-six elite junior soccer players were assessed between 2015 and 2017. Ninety-six elite junior soccer players (at time of match: age, 15.8 ± 0.9 years; body mass, 69.1 ± 8.0 kg) were assessed during 61 games within the 2015, 2016, and 2017 season, for a total of 441 individual match observations (4.8 ± 3.3 matches per player, range 1-13). Participants were classified by age group: under 15 (U15, n = 121, 14.7 ± 0.3 years), under 16 (U16, n = 176, 15.8 ± 0.3 years), or under 17 (U17, n = 144, 16.7 ± 0.4 years), and according to their playing position: Attacker (ATT), Defender (DEF), Mid-Fielder (MID), or Wide (WIDE). Participants wore global positioning system units during each match, where speed (m·min-1), acceleration/deceleration (m·s-2), and metabolic power (Pmet) were established. A 1- to 10-minute moving average was applied to establish the intercept (c) and slope (n) of running intensity variables as a power law y = cxn relationship. Linear mixed models were used to examine differences in the intercept and slope between age group and player position. There were no substantial differences in peak (intercept) or decline (slope) in running intensity between playing levels. Several differences were observed in the peak running speeds (m·min-1), particularly peak running speeds of ATT and DEF being substantially lower than the MID. Despite variability between positions, we suggest that the magnitude of these differences would not warrant the prescription of different running intensities across positions at the elite junior level. These findings describe the peak running intensities of elite junior soccer, useful in the monitoring and prescription of training to ensure that players are prepared for the most demanding periods of competition.